Transformation Of The Dynamics Of Village And Regency Political Power Relations In The Realm Of Village Expansion Policy In East Lombok Regency, Ntb - Saleh, Muh.; Kushandajani, Kushandajani; Yuwono, Teguh; Herawati, Nunik Retno (UNIVERSITAS PAKUAN, 2025)
This study aims to describe the dynamics of the power relations between villages and districts as the impact of village expansion in East Lombok Regency, West Nusa Tenggara, villages and how the construction of power relations must be carried out by villages and districts. The position of the village has been strengthened with the enactment of Law Number 6 of 2014 concerning Villages and the latest amendment with Law Number 3 of 2024. With this law, villages have a high level of confidence, for several reasons, including: the identity of villages and customary villages is clarified; the state recognizes authority based on the right of origin of the village and local-scale authority (subordination); villages are budgeted through the State Budget in the form of Village Funds (DD); The opening of opportunities for the emergence of new elites in the village as a result of political liberation. The method used is in the form of a qualitative approach with data collection techniques through interviews, observations, FGDs and document data analysis and analyzed using the Miles and Huberman model. The results of the study show that the dynamics of the power relationship between villages and districts in East Lombok are very dynamic; Villages are beginning to be consolidated internally because some of the resources they have and the pattern of mutually beneficial relations between villages and districts are rational choices to build power relations that strengthen each other in running the government.